К задаче о переходных процессах в цепных схемах с учетом особых разложений скачкообразных напряжений - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
The special expansions for input jumpwise voltages and their use in the calculation of transient processes in series circuits are shown. The calculation is made for the modes of idling and short circuit.